Plantar fascial fibromatosis and herpes zoster - Hsu, Chao-Yu; Ke, Der-Shin; Lin, Cheng-Li; Kao, Chia-Hung (PloS one, 2021)
Infection, chronic pain and depression are considered risk factors for herpes zoster (HZ). However, the correlation between plantar fascial fibromatosis (PFF) and HZ remains unknown. This study investigated HZ risk in patients with PFF. Data was extracted from the Longitudinal Health Insurance Database 2000, which is a subsample of the Taiwan National Health Insurance (NHI) Research Database and contains 1 million NHI beneficiaries. Between 2000 and 2012, patients diagnosed as having PFF were included in the case cohort. Every case was age and sex-matched with individuals without PFF through 1:4 frequency matching (control cohort). The end of the follow-up was defined as December 31, 2013, the date of HZ diagnosis, death, emigration, or withdrawal from the NHI program. In total, 4,729 patients were diagnosed as having PFF and were matched with 18,916 individuals without PFF. Patients with PFF were 1.23 times more likely to develop HZ than were those without PFF. Among those aged ≥65 years, patients with PFF had a higher HZ risk than did those without PFF (adjusted hazard ratio [aHR] = 1.48). Men with PFF had a significantly higher risk of HZ than did men without PFF (aHR = 1.44). Patients with PFF, particularly older and male patients, having a high HZ risk and may thus be vaccinated for HZ.